Fostering multiple document comprehension: motivational factors and its relationship with the use of self-study materials - Zink, Theresa; Hahnel, Carolin; Kroehne, Ulf; Deribo, Tobias; Mahlow, Nina; Artelt, Cordula; Goldhammer, Frank; Naumann, Johannes; Schoor, Cornelia (Zeitschrift für Erziehungswissenschaft, 2023)
Multiple document comprehension (MDC) is an essential skill for university students, making it beneficial to improve it. We assume that the value assigned to MDC is important to foster MDC since it can be a predictor for behavioral choices, such as working with self-study material. Using self-study material is typical for university learning, but it requires the motivation to improve a skill such as MDC. We define motivation to improve MDC in terms of expectancy, value, and cost to improve MDC. We expect that it is a driving force for working with self-study material on MDC, while it might also depend on the perceived value of MDC. Therefore, this study examined whether the perceived value of MDC predicts the motivation to improve MDC, which is also expected to predict the use of self-study material. A total of 278 students of different majors participated in a MDC assessment and received the opportunity to train their MDC skill with self-study material. The engagement in using the self-study material was measured by the total time and the number of page transitions on the self-study material. The results indicated that the perceived value of MDC partially predicted motivation to improve MDC. However, further analysis revealed mainly no significant effects of the perceived value of MDC and the motivation to improve MDC on the engagement in using the self-study material. However, the log data indicated that the engagement in using the self-study material was not as high as expected.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Log data; Motivation; Multiple document comprehension; Self-assessment; Self-study material; Value